Religiosity, self-control, and externalizing problems among juvenile offenders in Malaysia - Mohd Kadri, Norsyuhaidah (2018)
Adolescent externalizing problems may increase the likelihood of an unsuccessful transition to adulthood. Recent growths in adolescent misconduct have heightened the need to investigate the factors that may contribute to adolescent externalizing behaviour problem. A growing body of evidence has indicated religiosity to be important buffer for adolescent misbehaviour (Chamratrithirong et al., 2013; Desmond, Ulmer, & Bader, 2013; Pirutinsky, 2014). However, few studies have examined the mechanism whereby religiosity exerts this effect (Johnson, Jang, Larson, & De Li, 2001; Landor, Simons, Simons, Brody, & Gibbons, 2011). This study aims to examine a structural model on the relationship between adolescent religiosity and externalizing behaviour problem, and the mediation role of selfcontrol on this relationship. This study also seeks to examine whether the structural model is moderated by socio-demographic variables (age, gender, and family structure) and parental religious socialization (maternal and paternal). A quantitative and cross-sectional approach was employed in the present study. Data in this study was from a large-scale national research project led by Baharudin, Zulkefly and Zarinah (2015). The sample in this present study comprised of 427 juvenile offenders aged between 13 to 18 years from eight Sekolah Tunas Bakti (STB) across nation which recruited using stratified random sampling technique. Information of adolescent’s socio-demographic background, religiosity, self-control, rule-breaking behaviour, aggressive behaviour, maternal and paternal religious socialization were collected using self-report questionnaire. Data were analysed using Statistical Package for Social Science (SPSS) and Analysis of a Moment Structures (AMOS), and resulted in a structural model. The results of the direct effect indicated that adolescent religiosity influence both rule-breaking and aggressive behaviour problems. Whereas, the indirect effect showed that adolescent religiosity was significantly and indirectly linked to both externalizing problems through its impact on self-control. In addition, moderation analysis results indicated that this mediating mechanism showed significant difference across gender, suggesting female adolescent demonstrated higher buffering effect. However, this study found no significant moderation of adolescent’s age, family status, and parental religious socialization on the model. This study concludes that adolescent religiosity and selfcontrol have deterrent effect on adolescent externalizing problems. Nevertheless, the findings presented in the present study represent a further step towards developing preventative intervention programs aims at encouraging adolescent religiosity and self-control to protect adolescents against externalizing behavioural problems.